Crack Resistance and Mechanical Properties of Polyvinyl Alcohol Fiber-Reinforced Cement-Stabilized Macadam Base - Yi Zhao; Xuan Yang; Qingyu Zhang; Naixing Liang; Yangkai Xiang; Min Qin (Advances in Civil Engineering)
A series of tests were carried out to evaluate crack resistance and mechanical properties of polyvinyl alcohol fiber-reinforced cement-stabilized macadam, which is widely used as pavement base or subbase composite material. Three series of cement-stabilized macadam mixtures with cement content of 3.2%, 3.6%, and 4.0% were prepared by incorporating four various contents (0, 0.6, 0.9, and 1.2 kg/m3) and lengths (12, 18, 24, and 30 mm) of polyvinyl alcohol fiber. The optimum polyvinyl alcohol fiber content, fiber length, and cement content were determined based on the mechanical properties of cement-stabilized macadam mixtures. Then, unconfined compressive strength test, compressive resilience modulus test, splitting strength test, flexural tensile strength test, drying shrinkage test, and temperature shrinkage test were carried out in this study. The results show that polyvinyl alcohol fiber-reinforced cement-stabilized prepared by optimum proportions (cement 3.6%, fiber content 0.9 kg/m3, and fiber length 24 mm) has good crack resistance. The incorporation of polyvinyl alcohol fiber can effectively improve compressive strength and splitting strength, while its effect on CRM of cement-stabilized macadam is not remarkable. The anti-dry-shrinkage property and anti-temperature-shrinkage property of the specimens are also drastically improved due to the reinforcement effect of polyvinyl alcohol fiber. Moreover, the crack resistance index is proposed to evaluate the crack resistance of materials. The crack resistance of PVA fiber-reinforced cement-stabilized macadam prepared by optimum proportions is improved by 44.4%. Consequently, the mechanical properties and crack resistance of cement-stabilized macadam are obviously improved by adding polyvinyl alcohol fiber.